Estuarine ecohydrology - Wolanski, Eric; Elliott, M. (Michael), 1952 November 3- (Amsterdam : Elsevier Science, 2014)
Estuarine Ecohydrology, Second Edition, provides an ecohydrology viewpoint of an estuary as an ecosystem by focusing on its principal components, the river, the estuarine waters, the sediment, the nutrients, the wetlands, the oceanic influence, and the aquatic food web, as well as models of the health of an estuary ecosystem. Estuaries, the intersection of freshwater and coastal ecosystems, exhibit complex physical and biological processes which must be understood in order to sustain and restore them when necessary. This book demonstrates how, based on an understanding of the processes.
Estuarine water circulation -- Estuarine sediment dynamics -- Tidal wetlands -- Estuarine ecological structure and functioning -- Ecohydrology models -- Ecohydrology solutions.
CIP data; resource not viewed.
Includes bibliographical references and index.
Keywords: Ecohydrology; Estuarine ecology; NATURE -- Ecology; NATURE -- Ecosystems & Habitats -- Wilderness; SCIENCE -- Environmental Science; SCIENCE -- Life Sciences -- Ecology; Ecohydrology; Estuarine ecology; Electronic books; Electronic books